The impact of digital transformation on business strategies of seafood enterprises - The case of Ca Mau province - Luu, Đức Thượng (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2025)
The study focused on the level of digital transformation application and the impact of this process on the business strategy of seafood enterprises in Ca Mau province. Based on a survey of 103 enterprises and analysis of qualitative and quantitative data, the study showed that the level of digital transformation in the seafood industry is still uneven, mainly concentrated in large-scale enterprises, while the majority of small and medium-sized enterprises have only stopped at the initial stage of applying technology to some specific stages such as accounting, traceability or order management. Digital transformation has initially created positive changes in business strategy, helping to improve productivity, reduce costs and expand the market. However, businesses are still facing many challenges such as a shortage of technology human resources, financial constraints and a lack of a clear digitalization strategy. The topic also proposes a group of solutions on policies, training and technology investment to promote comprehensive digital transformation, helping seafood enterprises in Ca Mau improve their competitiveness in the context of the digital economy.